Ballistic thermoelectric transport in structured nanowires - Biao Wang; Jun Zhou; Ronggui Yang; Baowen Li (New Journal of Physics, 2014)
Thermoelectric (TE) devices are solid-state energy converters that can be used for power generation through the Seebeck effect and TE cooling through the Peltier effect. Nanostructures give great opportunities to engineer TE energy conversion efficiency. In this work, we investigate TE transport properties in structured nanowires (NWs) in the ballistic transport regime, where the NWs are bent, kinked, stubbed and segmented like a superlattice nanowire using the Green’s function method and the Landauer–Büttiker formula. A large Seebeck coefficient is found when the transmission gap appears due to the quantum interference effect of electrons. The sign of the Seebeck coefficient can be controlled by the geometries of these structured NWs. This finding is helpful for the design of nanoscale TE devices, such as thermocouple, with the same type of material doping rather than those comprised of n -type and p -type materials.